Relación entre conocimiento y comportamiento ambiental mediante una estrategia de educación ambiental en la Escuela Fiscal José Leonidas Delgado, cantón Rocafuerte-Manabí - Palma Alcívar, Arianna Michelle (2019)
The objective of the research was to evaluate the relationship between knowledge and environmental behavior through an environmental education strategy in students of the José Leonidas Delgado School of Law, canton Rocafuerte-Manabí. The total number of participating students was 57; represented the majority by children (37). The methods used were qualitative, quantitative and participatory action research. In addition, the application of techniques such as observation and test of questions was strategic since they were the main ones to evaluate the variables of the study. The first stage consisted in making a diagnosis of the initial knowledge and environmental behavior of the participants. For this, activities were developed such as: recognition of the study area, application of interviews with strategic actors and development of the initial questions test. The second stage was key in the study because through the application of environmental education strategies the environmental program was developed. This consisted of training on environmental issues to the development of practical activities of plastic waste management using the learn-doing methodology. During this stage, 3 reactions of the participants were also evaluated through checklist and observations. Finally, environmental knowledge was related to the environmental behavior of the students. The results showed a positive relationship in 7 out of 10 variables analyzed (p <0.05), especially in the knowledge of the effects of plastic in the soil and the behavior of not throwing plastic to the soil (0.011). It is concluded that environmental knowledge positively influences the environmental behavior of school students.